Barrier mechanisms in the Drosophila blood-brain barrier - Hindle, Samantha J.; Bainton, Roland J. (Frontiers in Neuroscience, 2014)
The invertebrate blood-brain barrier field is growing at a rapid pace and, in recent years, studies have shown a physiologic and molecular complexity that has begun to rival its vertebrate counterpart. Novel mechanisms of paracellular barrier maintenance through GPCR signaling were the first demonstrations of the complex adaptive mechanisms of barrier physiology. Building upon this work, the integrity of the invertebrate blood-brain barrier has recently been shown to require coordinated function of all layers of the compound barrier structure, analogous to signaling between the layers of the vertebrate neurovascular unit. These findings strengthen the notion that many blood-brain barrier mechanisms are conserved between vertebrates and invertebrates, and suggest that novel findings in invertebrate model organisms will have a significant impact on the understanding of vertebrate BBB functions. In this vein, important roles in coordinating localized and systemic signaling to dictate organism development and growth are beginning to show how the blood-brain barrier can govern whole animal physiologies. This includes novel functions of blood-brain barrier gap junctions in orchestrating synchronized neuroblast proliferation, and of blood-brain barrier secreted antagonists of insulin receptor signaling. These advancements and others are pushing the field forward in exciting new directions. In this review, we provide a synopsis of invertebrate blood-brain barrier anatomy and physiology, with a focus on insights from the past 5 years, and highlight important areas for future study.